Analisis Kemampuan Teknik Dasar Pemain Sepak Bola - Hasani, Birrul; Arifin, Ramadhan; Fauzan, Lazuardy Akbar (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This study aims to determine the level of mastery of basic techniques of GSI Banjarbaru players in playing soccer. The method used is qualitative descriptive research. The results of the study indicate that the passing technique is included in the category of "Very Good" with an average score of 9.23, the dribbling technique is "Good" with an average score of 18.45, the shooting technique is "Medium" with an average score of 9.05, and the heading technique is "Poor" with an average score of 3.88. Conclusion, GSI Banjarbaru players have the following basic soccer technique abilities: Passing technique is included in the Very Good category with an average point (9.23); Dribbling technique is included in the Good category with an average point (18.45); Shooting technique is included in the Moderate category with an average point (9.05); and for Heading technique is included in the Very Poor category with an average point (3.88). Keywords: Players, Soccer, Basic Techniques